PENGARUH DISIPLIN KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN PADA RSUD BESUKI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Kharisma, Ari Chandra; Ediyanto, Ediyanto; Minullah, Minullah (Fakultas Ekonomi dan Bisnis, 2024)
Work discipline is the most important element in employee performance, especially ASN who work in government agencies, especially in the health sector. Hospitals have an important role in increasing human life expectancy, for this reason hospitals have an important role in forming quality ASN. ASN in hospitals must be superior and competitive human resources through work discipline, compensation and work environment. The aim of this research is to analyze the influence of the variables Work Discipline, Compensation and Work Environment on ASN Performance at Besuki Regional Hospital with Work Motivation as an Intervening Variable. This research is explanatory research. The population in this study was ASN RSUD Besuki. The sampling technique uses total sampling. Data analysis and hypothesis testing in this research used Structural Equation Models – Structural Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.2.8 application, show that Work Discipline has a significantly positive effect on Work Motivation, Compensation has a significantly positive effect on Work Motivation, Work Environment has a significantly positive effect on Work Motivation, Work Discipline has a negative but not significant effect on Performance , Compensation has a positive but not significant influence on Performance, Work Environment has a positive but not significant influence on Work Motivation, Work Motivation has a positive but not significant influence on Performance, Work Discipline has a positive but not significant influence on Performance through Work Motivation, Work Discipline has a positive but not significant influence significant to Performance through Work Motivation, Work Environment has a positive but not significant influence on Performance through Work Motivation.